Patient‐reported postoperative pain, body image, and cosmetic satisfaction after transumbilical laparoendoscopic single‐site adrenalectomy. Issue 3 (1st February 2017) - Nomura, Takeo; Takei, Kohei; Abe, Satoki; Fukuda, Yuko; Yamanaka, Naoyuki; Sejiyama, Shinya; Yamasaki, Mutsushi; Shibuya, Tadamasa; Ando, Tadasuke; Mori, Ken‐ichi; Sumino, Yasuhiro; Sato, Fuminori; et al.
Abstract: Introduction: Laparoendoscopic single‐site surgery is a recently innovated urologic surgical procedure. Transumbilical laparoendoscopic single‐site adrenalectomy (LESS‐A) is technically safe and feasible in patients with benign adrenal tumors. To improve patient counseling and informed consent, we evaluated patient‐reported postoperative pain, body image, and cosmetic satisfaction after transumbilical LESS‐A. Methods: We reviewed 24 patients who underwent transumbilical LESS‐A and assessed their operative and esthetic outcomes and incisional pain. Incisional pain was evaluated using a 10‐point visual analog scale, and the body image and cosmetic satisfaction were measured using a questionnaire that included a body image scale (range, 5–20 points) and a cosmetic scale (range, 3–24 points). Results: Pure LESS‐A was performed on 10 patients using a multichannel port; an additional 5‐mm trocar was used in two obese patients. Supplementary to the single‐incision approach, one or two 3‐mm ports were used in 12 patients. The mean operative time was 203 min; the mean blood loss was 41 mL. The mean pain visual analog scale scores on postoperative days 1, 3, and 7 were 3.5, 2.2 ( P  = 0.012), and 1.5 points ( P  = 0.018), respectively. The mean body image scale and cosmetic scale scores indicating wound satisfaction 1 month after the surgery were 20 and 22 points, respectively. Although one patient had liver injury during surgery, the postoperative course during the 3‐month follow‐up was uneventful. Conclusion: Transumbilical LESS‐A confers less postoperative pain and better cosmetic satisfaction than conventional laparoscopic adrenalectomy. Therefore, this procedure could potentially become a standard treatment option for benign adrenal tumors.